2017
DOI: 10.18632/oncotarget.15327
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of miR-29a reduces the oncogenic properties of glioblastoma stem cells by downregulating Quaking gene isoform 6

Abstract: Glioblastoma is the most common type of malignant primary brain tumor and has high recurrence and lethality rates. Glioblastoma stem cells (GSCs), a subpopulation of glioblastoma cells, may promote rapid tumor recurrence and therapy resistance. Because altered microRNA (miR) expression in GSCs may lead to glioblastoma progression, we assessed the effects of miR-29a expression on the oncogenic behavior of GSCs. MiR-29a expression was lower in GSCs than non-GSCs, and overexpression of miR-29a in GSCs inhibited c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 32 publications
1
33
0
Order By: Relevance
“…Similar Results were reported by other study groups (Zhu et al, 2013;Gong et al, 2014;Xu et al, 2014) who reported a downregulation in miR-29a/29b levels in peripheral blood mononuclear cells and bone marrow from AML patients compared with healthy individuals. Also, miR-29a was found to be downregulated in many other types of neoplasms like lung cancer (Barkley and Santocanale, 2013), oral squamous carcinoma (Lu et al, 2014), glioblastoma (Xi et al, 2017), metastatic prostate cancer (Ahmed et al, 2013), ALK-positive anaplastic large cell lymphomas (Desjobert et al, 2011), endocrine-sensitive breast cancer (Muluhngwi et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Similar Results were reported by other study groups (Zhu et al, 2013;Gong et al, 2014;Xu et al, 2014) who reported a downregulation in miR-29a/29b levels in peripheral blood mononuclear cells and bone marrow from AML patients compared with healthy individuals. Also, miR-29a was found to be downregulated in many other types of neoplasms like lung cancer (Barkley and Santocanale, 2013), oral squamous carcinoma (Lu et al, 2014), glioblastoma (Xi et al, 2017), metastatic prostate cancer (Ahmed et al, 2013), ALK-positive anaplastic large cell lymphomas (Desjobert et al, 2011), endocrine-sensitive breast cancer (Muluhngwi et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…WTAP stimulates tumorigecity, migration and invasion of GBM cells possibly through enhancing the activity of epidermal growth factor receptor (EGFR), an important oncogenic factors in GBM [61]. In GSCs, WTAP also plays an important role as a downstream target of miR-29a/Quaking gene isoform 6 (QKI-6) axis-mediated inhibition of cell proliferation, migration and invasion, as well as promotion of apoptosis in GSCs [63].…”
Section: Rna M 6 a Writers In Gbmmentioning
confidence: 99%
“…In addition to controlling their own cleavage, localization, transport, stability, and degradation [13,14,[35][36][37], noncoding RNAs regulate the biological functions of cells, including the proliferation, infiltration, and metastasis of certain tumor cells [1,[17][18][19][20][21][22]. Surprisingly, it was revealed that noncoding RNAs also have a regulatory effect on m6A modifications [38][39][40][41]. Thus, concomitant targeting of m6A and noncoding RNAs may provide a synergistic effect in cancer therapy.…”
Section: Introductionmentioning
confidence: 99%